Murine Leukemia Virus Particle Assembly Quantitated by Fluorescence Microscopy: Role of Gag-Gag Interactions and Membrane Association - Andrawiss, Mariam (American Society for Microbiology, 2003)
In order to track the assembly of murine leukemia virus (MLV), we used fluorescence microscopy to visualize particles containing Gag molecules fused to fluorescent proteins (FPs). Gag-FP chimeras budded from cells to produce fluorescent spots, which passed through the same pore-size filters and sedimented at the same velocity as authentic MLV. N-terminal myristylation of Gag-FPs was necessary for particle formation unless wild-type Gag was coexpressed. By labeling nonmyristylated Gag with yellow FP and wild-type Gag with cyan FP, we could quantitate the coincorporation of two proteins into single particles. This experiment showed that nonmyristylated Gag was incorporated into mixed particles at approximately 50% the efficiency of wild-type Gag. Mutations that inhibit Gag-Gag interactions (K. Alin and S. P. Goff, Virology 216:418-424, 1996; K. Alin and S. P. Goff, Virology 222:339-351, 1996) were then introduced into the capsid (CA) region of Gag-FPs. The mutations P150L and R119C/P133L inhibited fluorescent particle formation by these Gag-FPs, but Gag-FPs containing these mutations could be efficiently incorporated into particles when coexpressed with wild-type Gag. When these mutations were introduced into nonmyristylated Gag-FPs, no incorporation into particles in the presence of wild-type Gag was detected. These data suggest that two independent mechanisms, CA interactions and membrane association following myristylation, cooperate in MLV Gag assembly and budding.